2016
DOI: 10.4155/fmc.15.175
|View full text |Cite
|
Sign up to set email alerts
|

Is Matching Ruthenium with Dithiocarbamato Ligands a Potent Chemotherapeutic Weapon in Oncology?

Abstract: In the last years, several metal-based compounds have been designed and biologically investigated worldwide in order to obtain chemotherapeutics with a better toxicological profile and comparable or higher antiblastic activity than the clinically-established platinum-based drugs. In this context, researchers have addressed their attention to alternative nonplatinum derivatives able to maximize the anticancer activity of the new drugs and to minimize the side effects. Among them, a number of ruthenium complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…Ruthenium exists in a distorted octahedral geometry with II to IV oxidation states which offers an attractive platform for developing new metal complexes for selective tumor therapy. , The biological potential of ruthenium complexes was first evaluated in the 1950s when Dwyer and co-workers recognized its anticancer activity. In 1980s, Clark and co-workers hypothesized the potential of Ru III complexes as selective antitumor prodrugs which can only be activated upon reduction into tumor tissues in the hypoxic and low pH environment . The synthesis of 65 (NAMI-A, Figure ), a Ru III complex in clinical trials (Phase I/II in combination with gemcitabine) as antimetastasizing agent, plausibly ruled out the above reduction-activating hypothesis, because the complex was inactive in vitro but more active in inhibiting the lung metastases in vivo. However, mechanistic studies showed that 65 can be reduced by GSH or ascorbic acid under physiological conditions to form its active Ru II species, resulting in an increase in antimetastatic activity of 65 , which is similar to Pt IV prodrugs .…”
Section: Endo-stimuli-responsive Metallodrugsmentioning
confidence: 99%
“…Ruthenium exists in a distorted octahedral geometry with II to IV oxidation states which offers an attractive platform for developing new metal complexes for selective tumor therapy. , The biological potential of ruthenium complexes was first evaluated in the 1950s when Dwyer and co-workers recognized its anticancer activity. In 1980s, Clark and co-workers hypothesized the potential of Ru III complexes as selective antitumor prodrugs which can only be activated upon reduction into tumor tissues in the hypoxic and low pH environment . The synthesis of 65 (NAMI-A, Figure ), a Ru III complex in clinical trials (Phase I/II in combination with gemcitabine) as antimetastasizing agent, plausibly ruled out the above reduction-activating hypothesis, because the complex was inactive in vitro but more active in inhibiting the lung metastases in vivo. However, mechanistic studies showed that 65 can be reduced by GSH or ascorbic acid under physiological conditions to form its active Ru II species, resulting in an increase in antimetastatic activity of 65 , which is similar to Pt IV prodrugs .…”
Section: Endo-stimuli-responsive Metallodrugsmentioning
confidence: 99%
“…However, the benefits of dithiocarbamate ligands are limited, because they have been related to potential hazards when they are not coordinated . With these considerations, many dithiocarbamate metallic complexes have been described able to combine the cytotoxic activity of the metal with the chemoprotective character of these ligands. The ability of these molecules to act as bidentate ligands affords high stability to the resulting metallic derivatives due to the so-called chelate effect, preventing from decomposition through loss of the dithiocarbamate ligand. Furthermore, gold­(III) is isoelectronic to platinum­(II), and both form four-coordinate square planar complexes, giving rise to the possibility of developing analogues to cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the immunosuppressive and anti-inflammatory properties of the gold ion itself [ 11 ] have made gold(III) complexes exciting for testing as anticancer compounds since the immune tumoral microenvironment became a target of anticancer therapy. On the other hand, ruthenium(III) complexes present several interesting aspects, such as (i) the rate of ligand exchange comparable to that of Pt(II) compounds [ 12 ], (ii) multiple and accessible oxidation states [ 13 , 14 ], and (iii) the ability to mimic iron in the physiological environment [ 15 , 16 ], which make this metal particularly interesting in the development of anticancer agents.…”
Section: Introductionmentioning
confidence: 99%